Peran Teknologi Digital Telemedicine dalam Meningkatkan Kualitas Pelayanan Kesehatan Masyarakat - Andi Sri Adinda; Nursuciyani Jamal (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Telemedicine is a significant innovation in modern healthcare, enabling the provision of remote healthcare services using telecommunications technology. This service allows medical personnel to conduct consultations, examinations, and even monitor patient conditions without face-to-face interaction. Implementations of telemedicine include video conferencing between doctors and patients, remote health monitoring using digital devices, and the use of integrated health applications on mobile devices. This technology offers significant opportunities to overcome geographical barriers, particularly for people living in remote, hard-to-reach areas, or with limited access to conventional healthcare facilities. This study aims to increase understanding of the role and benefits of telemedicine as part of the digital transformation in the healthcare sector to improve public health. The activities were conducted through lectures and demonstrations, structured in three stages: planning, implementation, and evaluation. During the planning stage, the implementation team prepared materials, media, and delivery strategies appropriate to the participants' level of understanding. The implementation stage focused on delivering educational materials related to the concepts, benefits, and examples of telemedicine applications in everyday life, followed by a demonstration session on the use of digital health applications. The final stage, an evaluation, measured participants' knowledge levels before and after the activity. The results showed a significant increase in students' understanding of telemedicine. The knowledge level increased from 23.0% before the training to 84.6% after the training. This increase demonstrates the effectiveness of the lecture method combined with interactive demonstrations in conveying information. Furthermore, students became more aware of the importance of utilizing digital health technology and felt more involved in the decision-making process regarding self-care.